IMPROVING THE STUDENT’S VOCABULARY MASTERY BY USING CONSTRUCTIVISM PRINCIPLE IN THE SECOND YEAR STUDENTS OF SMAN 1 KAUMAN - Budairi, Ahmad (Efektor, 2017)
Vocabulary plays important roles in mastering English. Vocabulary refers to all words in the whole language used in a particular variety. In this case, the students have some problems. The problems about difficult in mastering vocabulary, that the students are lack of vocabularies, the students often get difficult in expressing their ideas, the students have low motivation. The students felt unsatisfactory in their results. It’s caused the students are lack of practice and lack vocabulary to memorize it. In this case the good technique of vocabulary teaching is needed to make the students enthusiastic in learning vocabulary. The objective of vocabulary teaching in English as a foreign language cannot be separated from the objective of teaching English in general. In others words, the objective of teaching English implies the objective of teaching vocabulary.To overcome the problemin this study the researcher designs the media in the form of picture in teaching and learning activities. Finally, the pictures should be large enough and be easily seen by all students.There area number of ways to improve the students’ vocabulary mastery. Because of the condition the researcher holds the research related to the vocabulary’s mastery . The study is aimed at two main purposes as follows: (1) to improve the students’ vocabulary mastery through Constructivism principle(2) to improve the students’ interest in learning vocabulary through Constructivism principle.From the result of the study that Constructivism principle can improve the students’ vocabulary mastery and constructivism principle can improve the students’ interest in learning vocabulary